Leading for innovation leadership actions to enhance follower creativity - Mumford, Michael D. ca. 20./21. Jh; Newbold, Tanner R. ca. 20./21. Jh; Fichtel, Mark ca. 20./21. Jh; England, Samantha ca. 20./21. Jh (Cambridge University Press, 2022)
Creativity, the generation of novel and useful ideas, and innovation, the transformation of these ideas into new products, processes, and services, are both critical for the long-term viability, profitability, and growth of organizations. Moreover, the complex, risky, and uncertain nature of innovative efforts demonstrates the importance of organizational leaders to effectively manage the innovative process. In this element, we discuss the role of leaders in effectively facilitating the creative problem-solving process that gives rise to innovative products, processes, and services. More specifically, we highlight the knowledge, skills, and behaviors needed to effectively lead across three integrated facets of this process-leading the people, leading the work, and leading the firm. This discussion promotes an understanding of how leaders manage those asked to engage in innovative efforts and, moreover, how leaders systematically integrate creative ideas within the organization to ensure the development and success of innovative products, processes, or services
Keywords: Transformational leadership; Organizational change; Führung; Innovationsprozess; Innovationsmanagement